Chinese Students' Beliefs about English Language and Their L2 Motivation - Huiyuan Gu; Larisa Nikitina; Jagdish Kaur (National Research Mordova State University, 2022)
Introduction. This study adopts a Global Englishes perspective to examine dimensions within beliefs about English language held by Mainland Chinese university students. It also assesses whether and how these beliefs impact the students' motivation to learn English (L2 motivation). Materials and Methods. A questionnaire survey was conducted among 460 students learning English as a Foreign Language at a large public university in Mainland China. The questionnaire contained 28 items to assess the students' language beliefs and their L2 motivation. One section of the questionnaire gathered demographic information about the respondents. The research instrument was approved by the University's Research Ethics Committee. Exploratory factor analysis and multiple regression analysis were performed to analyze the data. Results. The Exploratory factor analysis identified four distinct dimensions within the language learners' beliefs, namely, Beliefs about Standard English, Beliefs about Global Englishes, Beliefs about English language education and Beliefs about China English. Three dimensions were identified within the students' L2 motivation, namely, International posture, Integrative orientation and Instrumental orientation. The ensuing regression analysis detected positive and statistically significant relationships between some dimensions in the language beliefs and L2 motivation. Particularly, Beliefs about English language education were found to have the strongest impact on L2 motivation. Discussion and Conclusion. The findings from the exploratory factor analysis support the views that languagerelated beliefs have distinct dimensions. They also give empirical evidence to the validity of the Global Englishes notion. From a language teaching perspective, the findings highlight the need to adopt GE-oriented pedagogies.